MASKING ANTI-PHAGOCYTIC SIGNAL OF TUMOR BY PRO-PHAGOCYTIC SIGNAL-A KEY TO IMMUREMENT OF CANCER CELL - Suresh, Madheswaran; Gurusamy, Malarvizhi; Sudhakar, Natarajan (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Immune surveillance is a mechanism where cells and tissues are watched constantly by ever alerted immune system. Most incipient cancer cells are recognized and eliminated by the immune surveillance mechanism, but still tumors have the ability to evade immune surveillance and immunological killing. One greater arm that tumor use to evade immune surveillance, is by expressing anti-phagocytic signal (CD47). Here we present a provocative hypothesis where cancer cells are removed alive by phagocytic cell (DC). That in turn will elicit effective and higher immunogenic condition. All this could be possible by addition pro-phagocytic signal (PtdSer) over cancer cell surface (Breast Cancer), that mask the presence of anti-phagocytic signal (CD47). In other words, adding eat me signal (PtdSer) over the breast cancer cell surface that mask the presence of don't eat me signal or anti-phagocytic signal present in breast cancer cell surface. This could be possible by using bi-specific antibody, conjugated to PEG-modified liposomes, which carry (PtdSer) pro-phagocytic signal (or) eat me signal, which target both CD47 and EGFRVIII on breast carcinoma. The simultaneous masking of anti-phagocytic signal, and adding of pro–phagocytic signal over cancer cell, will enhance the phagocytic clearance of live tumor cell and elicit immunological killing.